2010
DOI: 10.3348/kjr.2010.11.5.522
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Features of Benign Adenomyoepithelioma of the Breast

Abstract: ObjectiveThe purpose of this study was to evaluate the ultrasonographic features of benign adenomyoepithelioma of the breast.Materials and MethodsBetween 2005 and 2009, five patients had histologically confirmed adenomyoepithelioma of the breast. We retrospectively evaluated the ultrasonographic findings of the tumors in correlation with the pathology, and reviewed medical records.ResultsThe clinical manifestations included a palpable mass in three patients, while mammographic screening helped detect abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
12
1
2
Order By: Relevance
“…Mammographic findings of benign adenomyoepithelioma in previous reports were nonspecific. The tumors were reported as oval or irregular, relatively circumscribed or indistinct, and isodense or hyperdense 8–11. Our study also showed nonspecific mammographic findings.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Mammographic findings of benign adenomyoepithelioma in previous reports were nonspecific. The tumors were reported as oval or irregular, relatively circumscribed or indistinct, and isodense or hyperdense 8–11. Our study also showed nonspecific mammographic findings.…”
Section: Discussionsupporting
confidence: 57%
“…Because adenomyoepithelioma is rare, most reports in the literature describing its imaging appearances are individual case reports or studies of fewer than 5 cases 8–14. The purpose of our study was to retrospectively evaluate the mammographic and sonographic (US) features of benign adenomyoepithelioma of the breast and to briefly review the literature.…”
mentioning
confidence: 99%
“…AME arises from myoepithelial and epithelial cells in the normal breast lobules and ducts [6]. These tumours are characterised by biphasic proliferation of epithelial and myoepithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos en la mamografía son inespecíficos apareciendo generalmente como masas circunscritas, sin calcificaciones intratumorales en su mayoría catalogados como BIRADS 4, mientras que lesiones mal delimitadas con presencia de microcalcificaciones hacen sospechar al radió-logo un comportamiento maligno. En la ecotomografía por su parte se reconoce como un nódulo hipoecoico relativamente bien circunscrito pudiendo presentar refuerzo posterior y en raras ocasiones cambios quísticos (Tavassoli;Catena et al;Lee et al;Howlett et al, 2003).…”
Section: Discussionunclassified
“…El adenomioepitelioma es un infrecuente tumor de la mama, conformado por una proliferación bifásica de cé-lulas epiteliales y mioepiteliales (Chu et al, 2006;Lee et al, 2010;Rosen, 1987). La mayoría de estos tumores presentan un comportamiento benigno, sin embargo, en raras ocasiones presenta degeneración maligna (Catena et al, 2008).…”
Section: Introductionunclassified